2014
DOI: 10.1002/jmv.23947
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of hepatitis C virus strains and risk factors associated with infection and viral subtypes among Iranian patients

Abstract: Hepatitis C virus (HCV) has infected approximately 170 million people worldwide. While the seroprevalence of anti-HCV antibody among Iranian blood donors is 0.13%, HCV infection is prevalent in 59-80% of Iranian injecting drug users. One hundred seventy-eight anti-HCV positive patients were referred to the Gastroenterology Department at the Taleghani Hospital (Tehran, Iran) between June 2007 and June 2012. Out of 178 samples, 142 were positive for HCV-RNA. HCV subtypes were determined using phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…61,62 The transfusion of contaminated blood products is particularly associated with HCV genotype 1b and 2a infections 61,63 and HCV genotypes 1a and 3a are most common among PWID. 61,[64][65][66][67][68][69][70][71][72][73] Blood product screening over the past two decades or more has led to a decrease in the prevalence of HCV genotypes 1b and 2a. During the same period, genotypes 1a and 3a have increased in prevalence, particularly among PWID.…”
Section: Hcv Diversity and Genotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…61,62 The transfusion of contaminated blood products is particularly associated with HCV genotype 1b and 2a infections 61,63 and HCV genotypes 1a and 3a are most common among PWID. 61,[64][65][66][67][68][69][70][71][72][73] Blood product screening over the past two decades or more has led to a decrease in the prevalence of HCV genotypes 1b and 2a. During the same period, genotypes 1a and 3a have increased in prevalence, particularly among PWID.…”
Section: Hcv Diversity and Genotypesmentioning
confidence: 99%
“…During the same period, genotypes 1a and 3a have increased in prevalence, particularly among PWID. 61,64,[67][68][69][70][71][72][73] In addition, a group of endemic HCV strains exist, such as genotype 6 in southeast Asia and genotype 5 in Africa, which have a more restricted geographic distribution and are less prevalent than HCV genotypes 1, 2 or 3. 62 Finally, the last major group of strains reflect local epidemics and are highly prevalent in specific locations and risk groups, such as genotype 4d, which >10% of the Egyptian population are infected with (initially via contaminated medical devices) 74 and is also prevalent globally among HIV and HCV co-infected men who have sex with men.…”
Section: Hcv Diversity and Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied all available nucleotide sequences reported from Iran and other EMRO and Middle Eastern countries. Out of seven studies from Iran, four studies were published in 2004 - 2014 (33-36) and three were unpublished. Furthermore, 15 published and unpublished studies from EMRO and Middle Eastern countries including Afghanistan (37), Azerbaijan, Cyprus (38, 39), Egypt, Morocco (40), Pakistan (41), and Tunisia (42, 43) were collected.…”
Section: Resultsmentioning
confidence: 99%
“…Two important factors including cytokines and chemokines are the main players in the promotion of hepatitis C. These factors have been documented to have key roles in the regulation of innate and adaptive immune response to HCV infection (36)(37)(38). Multiple studies have found cytokines gene polymorphisms influence on the pathogenesis of HCV and outcome of response (39,40). In the literature review, the key roles of the most important host factors associated with HCV infection along with all related genes will be discussed.…”
Section: Host Factorsmentioning
confidence: 99%